Aplicação web utilizando API Google Maps - Schmitt, Peterson Ricardo Maier (2013)
This paper presents a study and development based on Google Maps API for Web development, showing brief historical concepts of relational databases, geographic database, Google Maps API, PHP, Postgre. At the end show examples of an application using the resources mentioned above, aimed at ease in various research locations with greater success and reliability.